Gass kopi / Aiman Shafiq ...[et al.] - Zainudin, Aiman Shafiq (2023)
This partnership-based corporation has five (5) individuals that have significant positions within the organization, including the general manager who also serves as the administration manager, marketing manager, operational manager, and financial manager. Our business company is called “Gass Kopi”. The word Gass literally means "let's go." Teenagers and young people in Indonesia utilize it frequently. Before, they would simply use the word "gas," which has the same meaning as "gaskeun." Besides, the word Kopi is known as Malaysian coffee. The local “kopi” is normally served in the local coffee shop or known locally as Kopitiam. “Kopi” is local language for coffee and “tiam” is the hokkien word for shop. So Kopitiam is known as Coffee Shop. So that, with the combination in our company name, we want to welcome the society to taste our special coffee and pastry. “Gass Kopi” Looking to start in Tapak Penjaja, Jalan Sena 10, Taman Rinting, 81750 Masai, Johor. This location very potentially because it will become a favorite place for people who want to lunch or grab some coffee during their break. Usually, the people who came this place consist of student, worker and parents who just pick up their child from school. The peak hour for this place is during lunch hour, during 12:00 pm until 3:00 pm. By this hour, this place will be visited by many people. On June 5, 2023, our business service will go into operation. In five years, “Gass Kopi” will become the top rank in our local product and franchise.